Monitoring water saturation changes using new seismic attribute in a 4D seismic study: An example in malaysian field - Rezaei, S. (Offshore Technology Conference, 2020)
4D seismic (time-lapse) is being used by oil and gas companies as a great tool for improving reservoir management. This technique is consist of repeated 3D seismic surveys captured at different times over same area. 4D seismic technology provides valuable information regarding spatial fluid movements which helps to overcome the challenges that the traditional surveillance methods are unable to solve and in addition it increases the ability of imaging fluid movement between wells after production and injection activities. This paper therefore focuses on 4D seismic method to estimate fluid saturation changes in a producing hydrocarbon reservoir after six years of production and water injection activities. The feasibility of new seismic attributes known as SQp and SQs (lithology and fluid indicator respectively) as a reservoir monitoring and management tool is analyzed and presented which shows the ability of SQp and SQs attributes to detect reservoir fluid saturation changes due to production and water injection activity in the field. To reach our objective, first deterministic seismic inversion was performed to extract seismic properties including Vp, Vs and Density for both base and monitor surveys. Base and monitor surveys were acquired in 1996 and 2006, respectively. Then the inversion results are being used to estimate SQp and SQs attributes volumes. In the final step estimated SQp and SQs attributes are used as an input in neural networks modelling for water saturation prediction. Based on the result of estimated water saturation and seismic attributes the fluid saturation changes was mapped, monitored and compared. Copyright 2020, Offshore Technology Conference